Analysis of the Role of Leadership and Work Discipline in Increasing Employee Productivity at the Nganjuk Regency Cooperative and Micro Enterprise Service - Dewi, Fitriana; Soedjoko, Dodi Kusuma Hadi (Universitas Nusantara PGRI Kediri, 2025)
Research aim: This research aims to analyze the role of leadership and work discipline in increasing employee productivity at the Department of Cooperatives and Micro Enterprises and the extent to which leadership influences employee productivity Design/Methode/Approach: This research uses a qualitative approach with descriptive research type. Data was collected through in-depth interviews and observations. The subjects of this research were leaders and employees who were selected to gain an in-depth understanding of the dynamics of leadership and work discipline. Research Findings: The findings of this research reveal that the role of leadership and work discipline have a significant impact on increasing employee productivity. Effective leadership is able to provide clear direction and motivation to employees, while high work discipline encourages employees to be more consistent and responsible in carrying out their duties. Theoretical contribution/Originality: The theoretical contribution of this research lies in developing an understanding of the relationship between leadership, work discipline and employee productivity. This research integrates leadership theory and work discipline within a SWOT analysis framework, which provides a new perspective. These findings contribute to the development of human resource management theory in the public sector, especially in increasing employee productivity. Practitionel/Policy implications: This research recommends that organizations prioritize leadership development programs and establish a clear work discipline framework. These findings are relevant for public institutions that aim to optimize employee workforce performance. Research limitation: The limitation of this research lies in its focus only on the Nganjuk Regency Cooperatives and Micro Enterprises Service, so the results cannot be fully generalized to other agencies. Future research can expand the object of study to other agencies to compare the influence of leadership and work discipline on employee productivity in various contexts.